Volatile, quality and olfactory profiles of fresh-cut polignano carrots stored in air or in passive modified atmospheres. (February 2021) - Cozzolino, R.; De Giulio, B.; Pellicano, M.P.; Pace, B.; Capotorto, I.; Martignetti, A.; D'Agresti, M.; Laurino, C.; Cefola, M.
Abstract: Volatile organic compounds (VOCs), quality attributes (respiration activity, total phenols and antioxidant activity) and olfactory profile by electronic nose of fresh-cut orange and purple Polignano carrots stored in Air or passive modified atmosphere (pMAP) were examined until 14 days of storage. The pMAP storage reduced the respiration rate, preserving the antioxidant activity and total phenols of the carrots. Moreover, it enhanced the peculiar aromatic notes of these carrots, as showed by Principal Component Analysis (PCA), which allowed also to select the VOCs associated to fresh carrots and to samples stored in Air or pMAP. Predictive models of selected volatiles by electronic nose data were build running Partial least squares regression (PLSR). In orange carrots, six significant models were obtained for β-pinene, δ-elemene, γ-curcumene, cis α-bisabolene, cariophyllene oxide and α-cedrol. In the case of purple carrots, E-nose signals were able to predict only two terpenes, trans β-cariophyllene and myristicin. Highlights: Volatile Organic Compounds and quality traits assessed in Polignano carrots. Volatile markers of fresh-cut carrots in Air or passive Modified Atmosphere. Prediction of Volatile Organic Compounds by Electronic-nose using multivariate models. Modified atmosphere storage reduced respiration rate of fresh-cut Polignano carrots. 2-hexenal and 2-decenal are markers of freshness for purple Polignano carrots.